Attention‐deficit/hyperactivity disorder and sluggish cognitive tempo throughout childhood: temporal invariance and stability from preschool through ninth grade. (8th January 2016) - Leopold, Daniel R.; Christopher, Micaela E.; Burns, G. Leonard; Becker, Stephen P.; Olson, Richard K.; Willcutt, Erik G.
Abstract : Background: Although multiple cross‐sectional studies have shown symptoms of sluggish cognitive tempo (SCT) and attention‐deficit/hyperactivity disorder (ADHD) to be statistically distinct, studies have yet to examine the temporal stability and measurement invariance of SCT in a longitudinal sample. To date, only six studies have assessed SCT longitudinally, with the longest study examining SCT over a 2‐year period. The overall goals of this study were to assess the 10‐year longitudinal stability and interfactor relationships of ADHD and SCT symptoms among a community sample of children. Methods: Confirmatory factor analysis was used to assess the temporal invariance of ADHD and SCT symptoms in a large population‐based longitudinal sample (International Longitudinal Twin Study of Early Reading Development) that included children assessed at preschool and after kindergarten, first, second, fourth, and ninth grades ( n  =   489). Latent autoregressive models were then estimated to assess the stability of these constructs. Results: Results demonstrated invariance of item loadings and intercepts from preschool through ninth grades, as well as invariance of interfactor correlations. Results further indicated that both ADHD and SCT are highly stable across these years of development, that these symptom dimensions are related but also separable, and that hyperactivity/impulsivity and SCT are both more strongly correlated with inattention than with each other and show differential developmental trajectories. Specifically, even in the presence of latent simplex analyses providing support for the developmental stability of these dimensions, linear comparisons indicated that that mean levels of hyperactivity/impulsivity decreased with time, inattentive ratings were generally stable, and SCT tended to increase slightly across development. Conclusions: This study adds to the current literature by being the first to systematically assess and demonstrate the temporal invariance and stability of ADHD and SCT across a span of 10 years.